The interrelatedness of formal, non-formal and informal learning - Cameron, Roslyn; Harrison, J. (Adult Learning Australia Inc, 2012)
Definitions, differences and relationships between formal, non-formal and informal learning have long been contentious. There has been a significant change in language and reference from adult education to what amounts to forms of learning categorised by their modes of facilitation. Nonetheless, there is currently a renewed interest in the recognition of non-formal and informal learning internationally and in Australia. This has been evidenced through the New OECD Activity on Recognition of Non-Formal and Informal Learning and recent policy developments in Australia. These developments have implications for the recognition of skills derived from informal and non-formal learning, especially for those disadvantaged in the labour market. This paper reports on data from a learning grid in a Learning Survey of labour market program participants (n = 172) from northern New South Wales and southern Queensland. We find that life (informal learning) and work experience (non-formal learning) are relatively more important for gaining self-reported skills than formal training/study. We conclude by arguing for a holistic focus on the dynamic interrelatedness of these forms of learning rather than being constrained by a deterministic dichotomy between formality and informality.